New Approach to International Competitiveness of Multi‑layer Enterprises. A Reference to Macroeconomic Models for the Assessment of Competitiveness as a Benchmark - Rosińska-Bukowska, Magdalena (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The author of this paper has demonstrated that in the period of the ongoing globalization new challenges regarding the creation of competitiveness have appeared. The purpose of this paper is to highlight the need for a new look at the issues of international competitiveness in the era of globalization and the necessity to focus efforts on creating a competitive system which results from actions at the micro‑, meso‑, macro‑ and meta‑economical levels. The author has presented the concept of systemic competiveness as a new approach to the assessment of international competitiveness of multi‑layer enterprises. The author has tried to express that it is the most important challenge for all kinds of participants on the global market, since, for each of them, the determinants of the surrounding environment are both new and the same. The paper is divided into four substantial parts and also includes an introduction and a summary. The first part of the article includes a reflection on the current challenges in the globalization process and requirements for international competitiveness in the era of corporate globalization – the current level in a developing of globalization process. The second part includes the theoretical concepts of competitiveness in compound organizations according to five concepts of international competitiveness. In the subsequent part, the author refers to a concept of five layers of the capital of organizations, which constitute pillars of the creation of competitiveness in the current economy, especially in multi‑layer enterprises. In the final part of article the author has shown the general assumptions of the concept of systemic coopetitiveness.